PATIENTS WITH PARAFUNCTIONAL HABITS: ASSESSMENT OF THE PSYCHOLOGICAL STATUS AND ITS REPERCUSSIONS BEFORE ORAL AND MAXILLOFACIAL SURGERIES - Monteiro Chaves Bernardo, Bárbara; da Silva Leitão, Brenda; Gabriele Martins Soares, Victória; Eudes Lorena Sobrinho, José; Quirino de Almeida Azevedo, Marcella (Health and Society, 2022)
Introduction: Parafunctional habits are behaviors that are not part of the functional and physiological needs of the components of the stomatognathic system and can be indicative of stress, anxiety and/or depression. They can generate complications during and after oral and maxillofacial surgeries. Objective: To estimate the prevalence of parafunctional habits and psychological status in patients undergoing oral and maxillofacial surgeries, their associated factors and their interference with the course of the dental procedure. Material and Method: The study is a field research, characterized by being observational, with a cohort design, with a quali-quantitative approach. A stratified probability sampling was carried out in patients from the CEO of surgery at Asces-Unita and the Clínica Ortoestetica de Toritama, to verify if there are factors in public and private care that may interfere during and after oral and maxillofacial surgeries.The research instruments were questionnaires based on the Beck Depression. Inventory-BDI, the Beck Anxiety Inventory-BAI, the LIPP Stress Symptoms Inventory. Results and Discussion: 116 patients were interviewed, among which 88 (75.86%) are from the Surgery CEO of the Centro Universitário Tabosa de Almeida-ASCES UNITA and 28 (24.13%) are from the Orthoesthetic Clinic of Toritama/PE. Of those interviewed, 64 (55.17%) patients had some parafunctional habit, 61 (52.58%) patients had some psychological disorder and 68 (58.62%) patients had some surgical complication. Factors such as stress, anxiety and depression can impair the surgical process as well as the patient’s recovery, generating a greater probability of episodes of high blood pressure, more intense bleeding in surgeries and a reduction of immune resistance, as well as leading to disorders psychosomatic. Conclusion: Thus, after crossing the variables, it was confirmed that there is a relationship between surgical complications with parafunctional habits and psychological disorders.